The effect of tax amnesty and the effectiveness of e-filling on individual taxpayer compliance at the pratama tax service office Sidoarjo Selatan - Beata Jenasari; Aloisius Hama (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of tax amnesty policies and the effectiveness of E Filling. on individual taxpayer compliance at the South Sidoarjo Primary Tax Service Office.This research is a type of quantitative descriptive research. The population of this study is the tax amnesty policy, and the effectiveness of E Filling. In this case, the unit of analysis is the individual taxpayers registered at KPP Pratama South Sidoarjo as many as 6,507 people, the total number of respondents in this study is 100 people. Based on the results of research and hypothesis submission of 100 individual taxpayers registered at the South Sidoarjo Primary Tax Service Office, the following conclusions can be drawn: The better the tax amnesty policy enacted by the Indonesian government, the more individual taxpayer compliance will increase. The effectiveness of E Filling has a significant or real effect on increasing individual taxpayer compliance.